2004
DOI: 10.1185/030079903125003026
|View full text |Cite
|
Sign up to set email alerts
|

Use of transdermal fentanyl without prior opioid stabilization in patients with cancer pain

Abstract: Transdermal fentanyl is an effective and well-tolerated treatment for cancer-related pain for patients regardless of whether they have previously received opioids. Previous guidelines have often advocated initial dose finding with short-acting opioids but this study demonstrates that such a complex titration and conversion schedule may not be necessary,and that treatment may be initiated directly with long-acting formulations such as transdermal fentanyl when previous analgesic therapy fails to provide adequat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
2
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 12 publications
5
21
2
1
Order By: Relevance
“…Other authors [23,24] found that, when switching to TF, the frequency of adverse events was slightly higher among opioid-naïve patients compared with the strong-opioid and weak-opioid groups. Moreover, the authors suggest that patients who require strong opioids for pain relief may receive transdermal fentanyl without a prior stabilization phase [23,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors [23,24] found that, when switching to TF, the frequency of adverse events was slightly higher among opioid-naïve patients compared with the strong-opioid and weak-opioid groups. Moreover, the authors suggest that patients who require strong opioids for pain relief may receive transdermal fentanyl without a prior stabilization phase [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the authors suggest that patients who require strong opioids for pain relief may receive transdermal fentanyl without a prior stabilization phase [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Fentanyl, a synthetic opioid, was developed in the 1960s and has been in clinical use for more than 30 years as a component of anesthetic regimens. 4 Initial limitations to its use included rapid onset of action and short duration of action. Newer transdermal and transmucosal routes of administration have lead to longer periods of analgesia.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent literature reports suggest that certain patients who are not tolerant to strong opioids, and even opioid-naïve patients, may safely receive a low-dose transdermal fentanyl device [84,85]. The approach of slowly escalating from a 12.5 or 25 μg/hour transdermal device should provide a degree of safety from opioid overdose.…”
Section: Therapeutic Considerationsmentioning
confidence: 99%